2019
DOI: 10.18488/journal.61.2019.73.146.157
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers Professional Development through Four-Step Problem-Solving Model: A Seminar Method

Abstract: Effective teaching and learning strategy is one of the most important topics in the field of teachers" professional development. Teachers" education and pre-service teachers" training programmes provide necessary coursework, field experience, and student teaching internship experience to pre-service, potential, and second career teachers who are seeking initial license status. Due to the rapid developments in Hong Kong, China, school teachers face challenges, difficulties, and social problems due to excess enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In fact, the general inductive approach is a useful tool to narrow down large-size data information into meaningful groups and categories. Like many qualitative research studies [ 5 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], the researcher followed an inductive approach and direction to understand and read the data. Unlike case study, narrative approach, and grounded theory studies, the researcher could not follow any data analysis procedures of these methodologies due to the nature of the focuses and aims.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the general inductive approach is a useful tool to narrow down large-size data information into meaningful groups and categories. Like many qualitative research studies [ 5 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], the researcher followed an inductive approach and direction to understand and read the data. Unlike case study, narrative approach, and grounded theory studies, the researcher could not follow any data analysis procedures of these methodologies due to the nature of the focuses and aims.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last century, educational research studies have attributed the shortage of teachers to two significant trends, including significant turnover rate and retirement, particularly in international schools where the school leadership tended to recruit teachers with the appropriate teaching qualifications based on the educational system and taught curriculum for the school [38]. For international schools in remote regions, such as the archipelagic states in Oceania, school leadership needs to explore solutions to enhance recruitment and teacher retention [39].…”
Section: Long-term Difficulties For International School Recruitmentmentioning
confidence: 99%
“…Second, there is an ambivalent attitude towards analyzing the psychological impacts of the contextual factors in teachers' professional development. Third, most researchers [11,[77][78][79] focused on pre-service or early career teachers instead of experienced in-service teachers. Fourth, there are inadequate research studies on examining personal and contextual factors synchronically and diachronically.…”
Section: Identification Of Relevant Research Gapsmentioning
confidence: 99%
“…Currently, research studies [11,12] on teachers' professional development and career choices showed some limitations in alleviating the shortage problems. Researchers [13][14][15][16] oversimplified factors or reached one-size-fits-all solutions too quickly.…”
Section: Introductionmentioning
confidence: 99%